2021
DOI: 10.1097/aln.0000000000003967
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint of General, Regional, and Combined Anesthesia for Total Knee Replacements

Abstract: Background Health care itself contributes to climate change. Anesthesia is a “carbon hotspot,” yet few data exist to compare anesthetic choices. The authors examined the carbon dioxide equivalent emissions associated with general anesthesia, spinal anesthesia, and combined (general and spinal anesthesia) during a total knee replacement. Methods A prospective life cycle assessment of 10 patients in each of three groups undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 37 publications
0
79
0
Order By: Relevance
“…For example, anaesthesia is a recognised carbon hotspot, 23 yet one MRI has approximately equivalent emissions to one gaseous general anaesthetic. 24 Thus far, however, the carbon emissions from imaging have received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…For example, anaesthesia is a recognised carbon hotspot, 23 yet one MRI has approximately equivalent emissions to one gaseous general anaesthetic. 24 Thus far, however, the carbon emissions from imaging have received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Health informatics can play a mitigation role in healthcare services' general carbon-emitting practices in several ways. One is by directing health data science efforts toward this; examples show how it is possible to model the emission consequences of decisions in surgical anesthesia and in intensive care, using industrial life cycle assessment software ( 22 , 23 ). Another approach is to support the expansion of virtual care, by refining telehealth platforms and tools: a systematic review found 14 studies from around the world claiming that telehealth reduces emissions as compared with in-person care, mainly by reducing travel-related fuel consumption.…”
Section: Health Informatics Is Needed To Reduce Healthcare's Carbon F...mentioning
confidence: 99%
“…For instance, opinions vary on whether it is safer to use plain white labels versus color-coded labels. 2 The use of prefilled syringes replaces the traditional errorprone process of placing several drugs into different syringes with a streamlined process whereby a manufacturer prepares numerous syringes of the same drug, while also incorporating standardized labeling. 3 Another practice is the use of label printers that legibly print the name and dose of the drug with a corresponding barcode that can then be scanned by a barcode reader before administration.…”
Section: An Improvement To Medication Safety-or a Weakness?mentioning
confidence: 99%
“…Thank you for the vivid cover art from Maria Koijck and Eva Glasbeek 1 that accompanied the pair of environmental pieces from McGain et al . 2 and Struys and Eckleman 3 in the December 2021 issue. While the discussion in the article 2 and editorial 3 of the carbon footprint of anesthesia help contextualize this issue, this cover art drives home the message in a striking fashion.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation